Evaluación de la gestión ambiental y calidad del servicio de agua potable en la comunidad de Padre Cocha. Loreto. 2022 - Diaz Trigoso, Gonzalo Rafael (2024)
The main objective of this research was to assess the perception of the Padre Cocha community regarding the environmental management of water use and the quality of drinking water service. The aim was to understand how environmental management practices and perceived service quality impact the sustainability of the water resource and community satisfaction with the drinking water service. The methodology employed in this study consisted of distributing structured surveys with closed-ended questions to residents with a Cronbach's alpha coefficient of 0.88 indicating excellent internal reliability of the assessment instrument. This suggests that the instrument's questions are coherent with each other and indicates that the responses obtained through the instrument are stable and consistent, which is essential for the validity of the research results. Data were collected on various dimensions of water management, including environmental sustainability, the effectiveness of treatment and conservation practices, and the quality of drinking water supply service. The sample included a representative selection of the population, ensuring the inclusion of diverse perspectives within the community, and the Spearman's Rho correlation reported a value of 0.786 and a p-value < 0.0001. The results revealed that the majority of the community positively perceives environmental management in the supply and treatment of drinking water. A significant positive correlation was observed between good environmental management practices and the perception of the quality of drinking water service. However, the results also highlighted concerns about the regularity of water supply and transparency in the communication of fees and bills. A considerable neutrality was noted in the responses, suggesting the need for more information and education for the community.